Automatic algorithm to obtain v sin i values via Fourier transform in the BeSOS database - Solar, Martín; Arcos, Catalina; Curé, Michel; Levenhagen, Ronaldo S; Araya, Ignacio (Monthly notices of the Royal Astronomical Society, 2022)
Be stars are found to rotate close to their critical rotation and therefore they are considered an important laboratory for the study of stellar rotation. In this context, we obtain the projected rotational velocity of a sample of classical Be southern stars in the BeSOS database via Fourier transforms in an automated way for several absorption lines at different epochs. A Gaussian profile is fitted to eight observed photospheric He i lines in order to select automatically from the profile the spectral signal given by areas under the curve of 95.45, 98.75, and 99.83 per cent, to obtain vsin i via the Fourier transform technique. The values obtained are in global agreement with the literature. Analysing only one line is not enough to set the vsin i value: depending on the line, the value in most cases is underestimated with respect to λ4471. When gravity-darkening effects are included, apparent values increase by ∼10 per cent. The resolution of the instrument Pontificia Universidad Catolica High Echelle Resolution Optical Spectrograph (PUCHEROS) used for BeSOS spectra ($R \sim 17\, 000$) constrains the theoretical lower bound possible to vsin i ∼ 100  km s−1. The procedure has limitations, using a linear limb-darkening function with ε = 0.6 for classical Be stars rotating close to the break-up velocity without gravity-darkening corrections, which cannot be negligible. Previous works measure vsin i values using just one spectral line and here we demonstrate that with more lines the results can vary. This could be due to the photospheric distribution of atomic transitions in classical Be stars.